Transcriptome Analysis and Identification of Genes Associated with Floral Transition and Flower Development in Sugar Apple (Annona squamosa L.) - Liu, Kaidong; Feng, Shaoxian; Pan, Yaoling; Zhong, Jundi; Chen, Yan; Yuan, Changchun; Li, Haili (Frontiers in Plant Science, 2016)
Sugar apple (Annona squamosa L.) is a semi-deciduous subtropical tree that progressively sheds its leaves in the spring. However, little information is available on the mechanism involved in flower developmental pattern. To gain a global perspective on the floral transition and flower development of sugar apple, cDNA libraries were prepared independently from inflorescent meristem and three flowering stages. Illumina sequencing generated 107,197,488 high quality reads that were assembled into 71,948 unigenes, with an average sequence length of 825.40 bp. Among the unigenes, various transcription factor families involved in floral transition and flower development were elucidated. Furthermore, a Kyoto Encyclopedia of Genes and Genomes pathway enrichment analysis revealed that unigenes exhibiting differential expressions were involved in various phytohormone signal transduction events and circadian rhythms. In addition, 147 unigenes exhibiting sequence similarities to known flowering-related genes from other plants were differentially expressed during flower development. The expression patterns of 20 selected genes were validated using quantitative-PCR. The expression data presented in our study is the most comprehensive dataset available for sugar apple so far and will serve as a resource for investigating the genetics of the flowering process in sugar apple and other Annona species.